PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 013 TELUK NILAP KEC. KUBU BABUSSALAM - Ma’aruf Ma’aruf; Hendri Marhadi; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was motivated by the low average grade science students learning outcomes SDN 013 Teluk Nilap Cooperative learning are two stay two stray learning is done by dividing the students into study groups formed by heterogeneous groups of four people each. The group then discussed with his group, after the completion of each group sent two of his friends to visit to find information kekelompok kekelompok neighbors then come back home to match the results of the discussion and concludes the discussion, then after the completion of each group presented the results of the discussion to the class in turn. This research was conducted in April by the number of students 24 people consisting of 13 men and 11 perempuan.Penelitian was conducted in two cycles, in each cycle is conducted 3 meetings, which consists of two times of the material and 1 replicates daily. The research instrument used is the syllabus, lesson plans, Lks, sheet teacher observation and student observation sheet. Student learning outcomes from basic score 63.96 increased to 77.50 in Deuteronomy End Cycle I with a percentage increase of 21.17% while the Deuteronomy End of Cycle I Cycle II Final Replay to increase to 86.67 occur with an increasing percentage of 35,50% , The completeness of student learning outcomes of students who complete basic score only 11 students with a percentage of 45.83% increase in the first cycle students who completed 18 students with a percentage of 75.00% and increased again in the second cycle students who completed the 22 people with percentage 91.67 %. Student activity increased in the second cycle of meetings III and IV, but not increased in the first cycle mungkan caused because the new learning model at present by the researcher. Increased activity of its teachers is increasing every cycle, the first cycle of the first meeting of its average amount is 66.67% Second meeting averaged 75% and will rise again in cycles III and IV into 87.50 and 91.67. After analyzing the research data by applying a type of cooperative learning model two stay two stray can improve learning outcomes fifth grade science students Elementary School District 013 Teluk Nilap Kec. Kubu Babussalam Keywords: Application of Learning Model TSTS, IPA Learning